2016
DOI: 10.1111/imb.12277
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ecdysone receptor, insect intestinal mucin and sericotropin genes by bacterially produced double‐stranded RNA affects larval growth and development in Plutella xylostella and Helicoverpa armigera

Abstract: RNA interference mediated gene silencing, which is triggered by double-stranded RNA (dsRNA), has become a important tool for functional genomics studies in various systems, including insects. Bacterially produced dsRNA employs the use of a bacterial strain lacking in RNaseIII activity and harbouring a vector with dual T7 promoter sites, which allow the production of intact dsRNA molecules. Here, we report an assessment of the functional relevance of the ecdysone receptor, insect intestinal mucin and sericotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Previous studies on Heliothis virescens revealed that exogenous dsRNA is not only readily degraded, but also lacks intracellular transport in larvae, reducing the efficiency of RNAi (Shukla et al, 2016). P. xylostella , on the other hand, has been successfully silenced by feeding droplets of dsRNA (Bautista et al, 2009) and bacterially produced dsRNA (Israni and Rajam, 2017). However, as a result of the absence of RNA-dependent RNA polymerases in insects, continuous feeding is required to maintain gene silencing (Scott et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Heliothis virescens revealed that exogenous dsRNA is not only readily degraded, but also lacks intracellular transport in larvae, reducing the efficiency of RNAi (Shukla et al, 2016). P. xylostella , on the other hand, has been successfully silenced by feeding droplets of dsRNA (Bautista et al, 2009) and bacterially produced dsRNA (Israni and Rajam, 2017). However, as a result of the absence of RNA-dependent RNA polymerases in insects, continuous feeding is required to maintain gene silencing (Scott et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We quantified ecdysone receptor ( EcR ) gene transcripts in nonparasitized and parasitized P. xylostella larvae (five replicates per treatment), and D. semiclausum symbiotic polydnavirus (PDV)‐related gene transcripts, namely vankyrin1 , vankyrin2 and viral innexin1 , in parasitized P. xylostella larvae (10 replicates per treatment). EcR is induced by the insect hormone ecdysone to control larval development and pupation (Israni & Rajam, 2017), while vankyrin1 , vankyrin2 and viral innexin1 are three of the best‐studied PDV‐related gene transcripts (Etebari et al., 2011). For these measurements, fourth‐instar larvae were individually pooled into TRIzol reagent (Invitrogen, Waltham, MA, USA) in 1.5 ml Eppendorf tubes, and then kept at 4°C before RNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, another study observed that feeding of dsRNA expressing live bacteria to larvae and adults of Plutella xylostella and H. armigera insects significantly compromised larval molting and mortality up to 50%. Treatment in adults resulted in 68% inhibition of oviposition and egg hatching, but neonates from surviving eggs showed no sign of transcript inhibition, indicating that application of live bacteria might affect the metamorphosis process . On the other hand, a study performed with S. exigua used both live and heat‐killed transgenic E. coli cells expressing β1 integrin dsRNA.…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Imentioning
confidence: 99%
“…Treatment in adults resulted in 68% inhibition of oviposition and egg hatching, but neonates from surviving eggs showed no sign of transcript inhibition, indicating that application of live bacteria might affect the metamorphosis process. 104 On the other hand, a study performed with S. exigua used both live and heat-killed transgenic E. coli cells expressing 1 integrin dsRNA. There was no difference in mortality rate (30-35%) with treatment using either live or heat-killed bacteria.…”
Section: Transformed Microorganisms and Virusesmentioning
confidence: 99%